Analisis Sengketa Tindak Lanjut Rekomendasi Ombudsman oleh Instansi Pemerintah: Pendekatan Hukum Administrasi: Penelitian - Taufiq, Muhtar; Doni Martien; Ismail (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The recommendations issued by the Ombudsman of the Republic of Indonesia carry legal authority that is final and must be followed up by government institutions, as stipulated in Law Number 37 of 2008. However, in practice, many of these recommendations are ignored or not implemented by the relevant agencies. This article aims to explore in greater depth the forms of disputes arising from non-compliance with Ombudsman recommendations, using an administrative law approach and actual case studies. A legal analysis is conducted on key provisions within Law No. 37/2008, Law No. 23/2014 on Regional Government, and Law No. 25/2009 on Public Services, to evaluate the effectiveness of the existing legal framework. This research applies a normative juridical method, supported by empirical data derived from annual Ombudsman reports and reports on recommendation implementation at the regional level. The findings reveal structural weaknesses in the follow-up mechanism, the absence of an integrated digital monitoring system, and the lack of enforceable administrative sanctions. Accordingly, this article recommends regulatory reforms, the development of a national digital monitoring system, and legal education for civil servants to strengthen the position of the Ombudsman as an effective external supervisor of public services. This study is expected to contribute significantly to enhancing the external oversight system of the government and promoting bureaucratic accountability in Indonesia.